Impact of feeding habits of Corsican red deer (Cervus elaphus corsicanus) on vegetation at Quenza Park in Corsica - Maillard, D; Casanova, J B; Gaillard, J M (MAMMALIA, 1995)
Following the translocation of Corsican red deer (Cervus elaphus corsicanus) in Quenza enclosures in 1985, we tried to assess the impact of red deer on woody mediterranean species. We found that sempervirent species with persistent leaves like Calytcotome villosa, Arbutus unedo, Quercus ilex and Cistus salviaefolius were eaten by deer all the year along. In fact, we identified three different categories of plant species according to the different levels of use by deer. A first groupe includes species highly and quickly consumed by deer like Calycotome villosa, Fraxinus ornus and Lonicera etrusca. These plants can even disappear when deer density becomes very high. A second group was composed of plant species red deer ate but searched for in a lesser extent like Arbutus unedo and Quercus ilex. Consumption of some of them showed a peak during summer (Rosa canina and Rubus sp.). in the last groupe, we pooled species weakly consumed by red deer, like Erica arborea and Cistus salviaefolius.
APS
Keywords: Arbutus unedo; Calytcotome villosa; Cervus elaphus corsicanus; Cistus salviaefolius; comsumption; Mediterranean; Quercus ilex; red deer